Significance Assessment of the Historic Maimon Palace Area. Issue 1 (April 2020) - Sitorus, R; Fitri, I
Abstract: During the last four decades, heritage significance assessment has become an important step in cultural heritage protection and management. It is essential to study cultural heritage significance and its assessment to develop the policies and planning, which will impact the conservation and the action in safeguarding cultural heritage in the future. Therefore, this research will explore the heritage significance of the historic Maimon Palace area through the historical and structural approach. It starts from documenting the existing, investigating the development of the historical place and formulating the statement of significance through group discussion meeting involving the local communities. The paper has presented the significance of the historic Maimon Palace area as a critical part of Medan city development, which is characterized by the Malay culture and Islamic identity. It is confirmed that Deli River, Derikhan Park, today is known as Seri Deli Park, and the Grand Mosque Al-Mashun are crucial elements surrounding the palace. The Maimon Palace's landmark is not only the landmarks for this area but also have remained a leading landmark for the city of Medan.